2013
DOI: 10.1111/ppc.12044
|View full text |Cite
|
Sign up to set email alerts
|

The Horror of Stigma: Psychosis and Mental Health Care Environments in Twenty-First-Century Horror Film (Part II)

Abstract: Practitioners should be aware of the specific manner in which clients are being stigmatized by the media. This paper highlights specific ways in which psychosis and MHCEs are stigmatized, and encourages practitioners to challenge these depictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…Similarly, Nour et al 24 found that most videos presenting schizophrenia on YouTube inaccurately portray the condition. Goodwin 25 examined the stereotyping of characters experiencing psychosis in 33 psychosis-related horror films released before the study was conducted. He concluded that 78.8% portrayed a homicidal maniac and 72.7% portrayed a pathetic or sad character.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nour et al 24 found that most videos presenting schizophrenia on YouTube inaccurately portray the condition. Goodwin 25 examined the stereotyping of characters experiencing psychosis in 33 psychosis-related horror films released before the study was conducted. He concluded that 78.8% portrayed a homicidal maniac and 72.7% portrayed a pathetic or sad character.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes towards people with mental illness are influenced by many factors, including culture, level of education, knowledge, and contact with people with mental illness [ 3 20 ]. Culture shapes family beliefs, media portrayals of people with mental illness and local health care provisions for mental health [ 4 , 6 ]. For example, mental illness is often perceived in many cultures as a sign of possession by evil spirits, moral weakness, a curse or a form of punishment by higher beings [ 7 , 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, entertainment media, such as prime time network TV shows and horror films, convey inaccuracies and promote stereotypes about mental illness (Goodwin, 2014) while medical TV talk shows, which blend facts and entertainment, offer accurate advice only 30% to 50% of the time (Thomas et al, 2018).…”
Section: Mediamentioning
confidence: 99%